Effect of the Escherichia coli EMO strain on experimental infection by Salmonella enterica serovar Typhimurium in gnotobiotic mice - J.V.M. Lima-Filho (Brazilian Journal of Medical and Biological Research, 2004)
An experimental infection with Salmonella enterica subsp. enterica serovar Typhimurium was evaluated in gnotobiotic mice previously exposed to a plasmid-free non-pathogenic Escherichia coli (EMO strain). Mice were exposed to EMO (experimental) or not (control) 10 days before challenge with Salmonella Typhimurium (10² colony forming units (CFU)/mouse). Survival after challenge was higher (P < 0.05) in the experimental group (16%) than in the control animals (0%). Histopathological examination of the colon and ileum mucosa of the experimental group showed less extensive lesions such as edema, cell inflammatory infiltration and hyperemia. The epithelial cells of the mucosal surface and the production of the mucous layer were also better preserved in the experimental group. The population levels of Salmonella Typhimurium in the feces were initially 10-fold lower (P < 0.05) in the experimental groups. However, 3 days after challenge both experimental and control groups showed similar population levels ranging from 10(8) to()10(9) CFU/g of feces. The intestinal contents of total and anti-Salmonella Typhimurium sIgA were higher in the experimental groups 10 days after inoculation of E. coli EMO strain. Translocation of Salmonella Typhimurium to the spleen was 10-fold lower (P < 0.05) in the experimental group only on day 3 after infection. This was not related to an increase in the bacterial blood clearance of the animals, as shown by experimental venous challenge with E. coli B41. In conclusion, treatment of mice with E. coli EMO strain promoted a relative protection against experimental infection with Salmonella Typhimurium. This protection was not due to the reduction of the population of pathogens in the intestine but was probably related to stimulation of the immune response.